Effect of Employing Vortex Generator on Curve Diffuser Performance - Anuar, Muhammad Musleh; Nordin, Normayati; Shariff, Muhammad Zahid Firdaus; Hariri, Azian; Mohamed Rasidi, Shamsuri; Hau, Chin Yong; Teo, Wen Yong (Journal of Advanced Mechanical Engineering Applications, 2021)
A diffuser is commonly applied in fluid-flow engineering applications with its simplest form of expanding area in the flow direction. A curve diffuser is one of its kinds often associated with secondary flow separation, thus improvement via installing passive flow control devices such as a vortex generator is to explore. The present work aims to numerically investigate the potential of four (4) types of vortex generators, i.e. triangle, rectangle, tapered, wishbone to improve the 90Â° curve diffuser performance. The results suggest that using vortex generators on a curve diffuser can improve performance. Triangle vortex generator provides the most optimum pressure recovery and flow uniformity of respectively 0.250 and 2.14.  This promises improvement of approximately 31.3% and 25.4% relative to the benchmark case, without vortex generator.